2013
DOI: 10.1371/journal.pone.0083825
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Diffusion Tensor Imaging after Acute Optic Neuritis Predicts Axonal and Visual Outcomes

Abstract: BackgroundEarly markers of axonal and clinical outcomes are required for early phase testing of putative neuroprotective therapies for multiple sclerosis (MS). ObjectivesTo assess whether early measurement of diffusion tensor imaging (DTI) parameters (axial and radial diffusivity) within the optic nerve during and after acute demyelinating optic neuritis (ON) could predict axonal (retinal nerve fibre layer thinning and multi-focal visual evoked potential amplitude reduction) or clinical (visual acuity and visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 38 publications
5
36
0
2
Order By: Relevance
“…After an initial decrease, AD values gradually increased back to normal AD values after a median of 18 weeks in MS ON patients. Longer AD normalization times were associated with more pronounced RNFL thinning and mfVEP amplitude loss at 12 months [111]. These findings suggest that optic nerve DTI AD values at ON baseline and the initial course of decreased AD values gradually increasing back to normal levels are biomarker candidates in MS patients to predict functional disability and putative recovery after acute ON.…”
Section: Optic Nerve Dti In Ms-onmentioning
confidence: 67%
See 2 more Smart Citations
“…After an initial decrease, AD values gradually increased back to normal AD values after a median of 18 weeks in MS ON patients. Longer AD normalization times were associated with more pronounced RNFL thinning and mfVEP amplitude loss at 12 months [111]. These findings suggest that optic nerve DTI AD values at ON baseline and the initial course of decreased AD values gradually increasing back to normal levels are biomarker candidates in MS patients to predict functional disability and putative recovery after acute ON.…”
Section: Optic Nerve Dti In Ms-onmentioning
confidence: 67%
“…On the other hand, FA values were reported to be initially normal and then to decrease over time [111,112]. These findings suggest simultaneous demyelination and axonal loss as well as possible reorganization processes to be present in the optic nerve after ON.…”
Section: Optic Nerve Dti In Ms-onmentioning
confidence: 91%
See 1 more Smart Citation
“…In fact, region-specific DTI measurements in MS patients have indicated a greater correlation of DTI changes in motor tracts with EDSS [20]. Importantly, it has been recently proposed that a reduction in axial diffusivity measurements of DTI correlate to extensive neuroinflammatorymediated axonal damage within the optic nerve following acute optic neuritis, often a primary indicator of MS [21]. Moreover, these investigators demonstrated that protracted reduction in axial diffusivity measurements correlated with pronounced retinal nerve fiber layer (RNFL) thinning and multifocal visual evoked potential (mfVEP) amplitude loss at 12 months.…”
Section: Current Imaging Techniquesmentioning
confidence: 99%
“…Among numerous advanced MR techniques Diusion-weighted image (DWI) and diusion tensor imaging Multiple system atrophy and progressive supranuclear palsy [5]. So far, DTI has been widely practical for the quantitative evaluation in many types of brain disease, including amyotrophic lateral sclerosis [6], schizophrenia [7], Parkinson's disease [8], NMO [9], and multiple sclerosis [10],and it has also been used in the quantitative evaluation of the optic nerves in normal brain [11], idiopathic demyelinating optic neuritis [12],and indirect traumatic optic neuropathy [13].…”
Section: Introductionmentioning
confidence: 99%